Penerapan CSR “The Green Care School Program” di Pertamina Integrated Terminal Balikpapan - Dwi Wahyu Hidayat; Edward Manaor Siahaan; Amalia Puspitasari; Susiana Susiana (Universitas Islam Darul Ulum Lamongan, 2020)
Corporate social responsibility (CSR) is a program where companies integrate social care in their business operations. Pertamina Integrated Terminal Balikpapan as a state-owned company plays an active role through its Corporate Social Responsibility program for the empowerment of communities around the company area. In this regard, this study aims to find out how the implementation of the CSR Program for Green Care School development at SMK N 6 Balikpapan, carried out by Pertamina Integrated Terminal Balikpapan. The results of this study indicate that the implementation of CSR programs implemented by Pertamina Integrated Terminal Balikpapan goes through five phases, namely the identification phase, the phase where social mapping is carried out by Pertamina Integrated Terminal Balikpapan to find out the potential that exists in the community, especially ring one. The preparation and analysis phase, the phase where designing the implementation of CSR systems such as sorting out programs or setting program goals. The approval phase, the phase in which the Pertamina Integrated Terminal Balikpapan presents the results of identification and analysis of social mapping. The implementation phase, the phase where the FGD begins for the selected program, the program is opened and runs with monitoring per activity. Evaluation phase, the final phase to assess the quality of programs that are run regularly. The ultimate goal of this program is to realize the centre of environment school.